Interleukin 6 promotes an in vitro mineral deposition by stem cells isolated from human exfoliated deciduous teeth. Issue 10 (31st October 2018) - Nowwarote, Nunthawan; Sukarawan, Waleerat; Kanjana, Kiattipan; Pavasant, Prasit; Fournier, Benjamin P. J.; Osathanon, Thanaphum
Abstract : Interleukin 6 (IL-6) plays various roles including stem cell regulation. The present study investigated the effect of IL-6 on cell proliferation, colony forming unit ability, stem cell marker expression and differentiation ability in stem cells isolated from human exfoliated deciduous teeth (SHEDs). We reported that the isolated cells from dental pulp tissues for deciduous teeth expressed CD44, CD90 and CD105 but not CD45. These cells were able to differentiate into osteoblasts, adipocytes and neuronal-like cells. IL-6 treatment resulted in the significant increase of NANOG, SOX2 and REX1 mRNA expression. However, IL-6 had no effect on cell proliferation and colony forming unit ability. IL-6 did not alter adipogenic and neurogenic differentiation potency. IL-6 supplementation in osteogenic medium led to a significant increase of mineralization. Furthermore, IL-6 upregulated ALP, ANKH and PIT1 mRNA levels. In conclusion, IL-6 participates in the regulation of pluripotent marker expression and is also involved in mineralization process of SHEDs. Hence, IL-6 could be employed as a supplementary substance in culture medium to maintain stemness and to induce osteogenic induction in SHEDs for future regenerative cell therapy.